Training report on Agroecology for AVFA trainers - Rudiger, Udo (International Center for Agricultural Research in the Dry Areas, 2022)
The report describes a six day training session on Agroecology and Permaculture. The training composed three days of theoretical and three days of practical training. Target group were agricultural trainers and extension agents